Upaya Peningkatan Kemampuan Literasi Siswa Di Kelas V SD Negeri 06 Rantau Bertuah Melalui Program Kampus Mengajar (Khirani: Jurnal Pendidikan Anak Usia Dini, 2023)
This research aims to describe efforts to improve the literacy skills of class V SD Negeri 06 Rantau Bertuah through a campus teaching program with research using the classroom action research approach method, which is a practical study that aims to overcome weaknesses in the learning process in the classroom. Through certain actions, the main goal is to improve and enhance learning in a more professional manner. Literacy, as a key aspect, is very significant in children's intellectual development. Literacy is a person's skills in reading, writing and understanding texts which are important for students' intellectual development. The teaching campus is one of the facilities that has great potential to make a significant contribution to improving literacy skills.